A novel SMARCA2-CREM fusion expending the molecular spectrum of salivary gland hyalinazing clear cell carcinoma beyond the FET genes - Lanic, Marie-Delphine; Guérin, René; Sater, Vincent; Durdilly, Pauline; Ruminy, Philippe; Skálová, Alena; Laé, Marick (Genes, chromosomes & cancer, 2023)
Hyalinizing clear cell carcinoma (HCCC) is a rare salivary gland carcinoma with a generally indolent behavior, characterized by recurrent chromosomal translocation involving EWSR1 (22q12.2) leading to two fusion genes EWSR1::ATF1 or EWSR1::CREM. We report one case of HCCC with a novel SMARCA2::CREM fusion, identified by targeted RNA next generation sequencing by LD-RT-PCR, which has until now never been described in salivary glands. The exon 4 of SMARCA2 is fused to exon 5 of CREM. This fusion has been described previously in only one tumor, a central nervous system tumor (intracranial mesenchymal tumor) but not in other FET::CREB fused tumors. This fusion was confirmed by CREM break-apart FISH and reverse transcriptase polymerase chain reaction (RT-PCR). The tumor cells showed retained expression of INI1, SMARCA2, and SMARCA4 by immunohistochemistry. We compare its clinical, histopathological, immunophenotypic, genetic features with those previously described in HCCC, FET::CREB fusion-positive. Our results added data suggesting that different histomolecular tumor subtypes seem to be included within the terminology "HCCC, FET::CREB fusion-positive," and that further series of cases are needed to better characterize them.
Keywords: fúzní onkogenní proteiny; Salivary Glands; Carcinoma; lidé; DNA-helikasy; DNA Helicases; Cyclic AMP Response Element Modulator; nádory slinných žláz; Transcription Factors; protein EWS vázající RNA; Humans; karcinom; modulátor elementu responzivního pro cyklický AMP; slinné žlázy; translokace genetická; transkripční faktory; Translocation, Genetic; jaderné proteiny; exony; RNA-Binding Protein EWS; Salivary Gland Neoplasms; Exons; Oncogene Proteins, Fusion; Nuclear Proteins